Respiratory protection and safety - Smith, Bo; The MARCOM Group, Ltd. ([Boothwyn, PA] : The MARCOM Group, Ltd., 2006)
This program explains on how the respiratory system works, potential effects of respiratory hazards, common types of respiratory hazards, common causes of respiratory problems, good respiratory safety practices and commonly used respiratory safety equipment
Title from container
Executive producer, Donald L. Leonard ; editor, Anthony Bosco
Narrator: Don Dawson
Keywords: Gas masks; Breathing apparatus; Human respiratory system; Health and safety